DZIENNIKARSTWO LOKALNE I SZTUCZNA INTELIGENCJA – WYBRANE ZAGADNIENIA. STUDIUM PRZYPADKU PORTALU TORREVIEJAONLINE.PL. - KIJKO, PAWEŁ; DOLIWA, URSZULA (Annals of Cultural Studies / Roczniki Kulturoznawcze, 2026)
The article examines a research experiment concerning the operation of the news portal torreviejaonline.pl, addressed to the Polish community in Spain, living mainly in Torrevieja and its vicinity. The portal’s functioning was based on the extensive use of AI tools. The aim of the study was to verify the feasibility of running an attractive news service by a single-person editorial team supported by generative algorithms. Using a practice-led research approach and data analysis spanning the years 2022–2025, the authors demonstrate that this model makes it possible to attract an audience exceeding the size of the local target community. The analysis shows that content with a high proportion of AI support(over 80% of the text) generates disproportionately high traffic compared to content produced using more traditional methods. The study also highlights the evolving role of the editor in this process. In the emerging model of journalism, the editor becomes primarily a designer and verifier of content, responsible for fact-checking as well as linguistic and quality control. The findings suggest that synergy between the efficiency of AI tools and human potential may offer an effective response to the challenges faced by contemporary local media.